Investigating the Effect of Narcissistic Tendencies on Marital Relationship Stability and the Mediating Role of Emotional Maturity in Couples - Raisi Sheykhvisi, Ahmad; Afrazizadeh , Seyed Faizullah; Maredpour, Ali Reza (Applied Family Therapy Journal (AFTJ), 2025)
Objective: The present study aimed to investigate the effect of narcissistic tendencies on marital relationship stability and examine the mediating role of emotional maturity in couples. Methods and Materials: This study employed a descriptive-correlational design and was conducted among married couples residing in Chaharmahal and Bakhtiari Province, Iran. A total of 384 couples were selected using multistage cluster sampling. Inclusion criteria included at least two years of marital experience and no history of severe psychological disorders. Data were collected using three standardized instruments: the Marital Instability Index (MII), the Narcissistic Personality Inventory (NPI), and the Emotional Maturity Scale (EMS). The psychometric properties of these tools were confirmed through Cronbach’s alpha and split-half reliability. Data were analyzed using descriptive statistics, Pearson correlation, and structural equation modeling (SEM) via SPSS and AMOS software. Bootstrapping was also employed to test the mediating effect. Findings: The results revealed that narcissistic tendencies were significantly and negatively associated with marital relationship stability (β = -0.32, p < .001). Emotional maturity was found to have a significant positive effect on marital stability (β = 0.43, p < .001) and a significant negative relationship with narcissistic tendencies (β = -0.38, p < .001). Importantly, emotional maturity partially mediated the relationship between narcissistic tendencies and marital stability (indirect effect β = -0.16, p < .01), and the total effect of narcissism on marital instability was substantial (β = -0.48, p < .001). The proposed model demonstrated a good fit to the data with acceptable fit indices. Conclusion: The findings suggest that narcissistic traits undermine marital stability directly and indirectly by reducing emotional maturity. Emotional maturity serves as a protective factor that enhances relational resilience. These results highlight the importance of addressing emotional development and personality traits in marital counseling and relationship education.